Missed appointments at a tuberculosis clinic increased the risk of clinical treatment failure - Sompong Srisaenpang (2018)
We investigated the charts of 381 new smear-positive tuberculosis patients at Khon Kaen Medical School during 1997-2001 using World Health Organization definitions to evaluate associations among treatment success or failure (defaulted, failed, died, or not evaluated) and tuberculosis clinic contact, demographics and clinical characteristics of the patients. Multinomial logistic regression was used for three-category outcome analysis: treatment success, transferred-out and clinical treatment failure. The treatment success and clinical treatment failure rates were 34.1% and 34.4%, respectively. About 46.5% and 85.8% of patients missed appointments at the tuberculosis clinic in the treatment success and treatment failure groups, respectively. The results show that patients who were absent from the tuberculosis clinic were 5.95 times more likely to have clinical treatment failure than treatment success, having adjusted for the effect of transfering-out and the effect of the treatment regimen and the sputum conversion status (adjusted odds ratio = 5.95; 95% CI: 2.99 to 11.84). The review showed that absence from the tuberculosis clinic was an independent risk factor for clinical treatment failure. We recommended that all new smear-positive tuberculosis patients should be followed closely at a tuberculosis clinic.